Sumbawa University Of Technology Infomatrix : Enhancing University Engagement Through An Intelligent Chatbot System - David T. Ndomaina; Shinta Esabella; I Made Widiarta; Nora Dery Sofya (Bulletin of Information Technology (BIT), 2024)
The aim of this research is to design and implement the chatbot system "Universitas Teknologi Sumbawa Infomatrix", which by utilizing the capabilities of Artificial Intelligence (AI) and Natural Language Processing (NLP) produces an interactive and efficient platform for students, facilitating access to comprehensive information about the university and helping makes it easier for students to get the right information to support their academic process on campus. Built web-based chatbot application, developed using the PHP programming language with the Laravel framework, integrated with a MySQL database, and utilizing Dialogflow cloud integration for machine and user conversation chat systems. This research methodology follows Angie Method and in system design, uses a structured design method that combines Context Diagrams, Data Flow Diagram (DFD), and Entity Relationship Diagram (ERD). The system testing uses a beta testing approach. With the presence of this Institutional Chatbot Application, it can make it easier for students to obtain UTS university data and information and become an effort to increase involvement at Sumbawa University of Technology through AI-based interactions.